2014
DOI: 10.1007/s00066-014-0689-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo dosimetry in intraoperative electron radiotherapy

Abstract: In vivo dosimetry can produce satisfactory results at every studied location with a general-purpose linac. Detector choice should depend on user factors, not on the detector performance itself. Surgical team collaboration is crucial to success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…MOSFET or microMOSFET dosimeters have been proposed for online in vivo dosimetry in IOERT procedures for different tumor types [ 13 15 ]. Gafchromic and radiochromic films wrapped in sterile envelopes for offline in vivo breast or rectal dosimetry [ 34 , 35 ] were also used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MOSFET or microMOSFET dosimeters have been proposed for online in vivo dosimetry in IOERT procedures for different tumor types [ 13 15 ]. Gafchromic and radiochromic films wrapped in sterile envelopes for offline in vivo breast or rectal dosimetry [ 34 , 35 ] were also used.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the very high planned dose in an IOERT treatment, in vivo dosimetry is highly recommended in order to: verify the correct delivery of irradiation; apply possible monitor units corrections and record the dose received by patients [ 12 ]. Dosimeters like MOSFETs and radiochromic films have been routinely used for this purpose [ 13 15 ]. Although thermoluminescent dosimeters (TLDs) are well-established for in vivo dose verification, their response to IOERT beams has not been yet investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The difficulty of inserting more than one MOSFET has also been identified elsewhere [ 24 ]. In addition, it has been pointed out that MOSFETs are presumably more difficult for the surgeon to initially handle because they have to be inserted with sterile components and attached onto the surgical bed [ 15 ]. Moreover, the compression placed on the MOSFET by the applicator can also move it [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fruitful experiences based either on metal oxide semiconductor field effect transistors (MOSFETs) [ 10 12 ], radiochromic films [ 13 , 14 ], or both [ 15 ] have been reported. However, information about in vivo dosimetry in intraoperative radiotherapy is somewhat scarce.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, publications on IOERT for applications outside the breast mostly report clinical results and do not describe dosimetric aspects (e.g [10,28]). Besides the work of Costa et al [29], who reported in vivo dosimetry for pelvis IOERT on a limited series of 32 patients, very few studies [4,30] report results of in vivo dosimetry outside the breast.…”
Section: Introductionmentioning
confidence: 99%